GECET: Garotas nas Engenharias, Ciências Exatas e Tecnologias: Projeto de Extensão voltado para a participação feminina nas áreas STEM - Benvenuto, Giovana A.; Brandi, Analice C.; Colnago, Marilaine; Ferreira, Rafaella S.; Picoli, Helen S. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e Web, 2024)
The GECET: Garotas nas Engenharias, Ciências Exatas e Tecnologias is an extension project linked to the São Paulo State University “Júlio de Mesquita Filho” (UNESP), with the aim of increasing female participation in STEM fields (Science, Technology, Engineering, and Mathematics). The project operates on several fronts to promote gender equity, ranging from basic education to higher education and postgraduate studies. The GECET has had a significant impact, increasing female interest in STEM fields, raising awareness about gender stereotypes, developing educational materials, and generating academic production with participation in congresses. The strategic use of social media was also essential for scientific dissemination and engagement, resulting in recognition and awards for the impact on promoting gender equity.